(untitled) (Journal of Advanced Research in Civil Engineering and Architecture, 2019)
In this research, an alternative technique to Gauss Elimination Method for Determinants is presented. It gives exact determinants. It is free of fractions, free of roundoff errors and can be applied for all types of square matrices. This alternative technique is illustrated in four different examples.